Audio Visual Based Learning Media in Learning the History of Human Life in the Pre-literacy Age in Indonesia - Pertiwi, Nurul Reza; Kumalasari, Dyah; Setiawan, Johan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The development of audio-visual-based learning media does not have problems with media limitations and students' low interest in the learning process. The aim of the study was to develop an audio-visual-based learning media in history learning, and the feasibility of audio visual based learning media in history learning. This research is Research and Development (R&D) with ADDIE model. The test subjects involved 36 students of class X IPA 4. Techniques and data collection instruments using questionnaires, observations, interviews, and documentation. The data analysis technique used qualitative and quantitative analysis. The results of the study the development of audio-visual-based learning media on material about pre-literate human life in Indonesia was made using the Adobe Photoshop application. The level of utilization of the results of the validation of media experts, and learning experts, respectively with an average result of 4.73 (very good), 4.28 (very good), 4.50 (very good), and student results of 4.37 (very good). In conclusion, the audio-visual-based learning media developed is feasible to be used as a historical learning media. The implication is that there is a change in positive attitudes and student interest in learning history.